The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/slct.202200212
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Corrosion Inhibition of Cactus cladode Extract and Effect of KI Addition on Mild Steel in 0.5 M H2SO4

Abstract: Adsorption and corrosion inhibitionof Cactus cladode(CC) extract collectedin eastern Algeria from areas of Chetaibi in Annaba on mild steel (MS) in 0.5 MH2SO4 solution were studied with potentiodynamic polarization (PP) and electrochemical impedance spectroscopy (EIS) measurements. The electrochemical stability of surface inhibitor film was investigated by chronoamperometry (CA) technique. The MS surface exposed to thecorrosive medium in the absence and presence of CC extract was examined by scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 82 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…Aloe polysaccharide extract (Zhang et al, 2020) was also investigated for corrosion inhibition abilities, where 800 mg/L produced an, I.E of 96% for mild steel. The extracts of Cactus cladode (Oulabbas et al, 2022) and Hibiscus sabdariffa (Ameer and Fekry, 2015) also showed promising IEs of 97.7% and 93.7% for mild steel in HCl media respectively. Many of these plant extracts adhere to the Langmuir adsorption isotherm, with either physical, chemical, or physiochemical modes of adsorption.…”
Section: Introductionmentioning
confidence: 95%
“…Aloe polysaccharide extract (Zhang et al, 2020) was also investigated for corrosion inhibition abilities, where 800 mg/L produced an, I.E of 96% for mild steel. The extracts of Cactus cladode (Oulabbas et al, 2022) and Hibiscus sabdariffa (Ameer and Fekry, 2015) also showed promising IEs of 97.7% and 93.7% for mild steel in HCl media respectively. Many of these plant extracts adhere to the Langmuir adsorption isotherm, with either physical, chemical, or physiochemical modes of adsorption.…”
Section: Introductionmentioning
confidence: 95%